Le Maître ignorant : cinq leçons sur l'émancipation intellectuelle - Rancière, Jacques 1940- (Paris Fayard, 1987)
'Le maître ignorant : cinq leçons sur l'émancipation intellectuelle' is a 1987 book by philosopher Jacques Rancière on the role of the teacher and individual towards individual liberation. Rancière uses the example of Joseph Jacotot, a French teacher in the late 18th century who taught in Belgium without knowledge of their language (Flemish), to explain the role of liberation after Marxism. The work expresses Rousseauist ideas, e.g. in the state of nature humans are morally good, and emphasizes that individual change precipitates societal change. Its arguments draw heavily from the French socialist party's debates on education during the 1980s.
Jacques Rancière (1940) is a French philosopher, Professor of Philosophy at European Graduate School in Saas-Fee and Emeritus Professor of Philosophy at the University of Paris VIII: Vincennes—Saint-Denis. After co-authoring Reading Capital (1965) with the structuralist Marxist philosopher Louis Althusser and others, and after witnessing the 1968 political uprisings his work turned against Althusserian Marxism, he later came to develop an original body of work focused on aesthetics.
Keywords: 20th Century (1901-2000); Philosophy; Education; France